Isolation of Intrinsically Active (MEK-independent) Variants of the ERK Family of Mitogen-activated Protein (MAP) Kinases - Levin-Salomon, Vered (American Society for Biochemistry and Molecular Biology, 2008)
MAPKs are key components of cell signaling pathways with a unique activation mechanism: i.e. dual phosphorylation of neighboring threonine and tyrosine residues. The ERK enzymes form a subfamily of MAPKs involved in proliferation, differentiation, development, learning, and memory. The exact role of each Erk molecule in these processes is not clear. An efficient strategy for addressing this question is to activate individually each molecule, for example, by expressing intrinsically active variants of them. However, such molecules were not produced so far. Here, we report on the isolation, via a specifically designed genetic screen, of six variants (each carries a point mutation) of the yeast MAPK Mpk1/Erk that are active, independent of upstream phosphorylation. One of the activating mutations, R68S, occurred in a residue conserved in the mammalian Erk1 (Arg-84) and Erk2 (Arg-65) and in the Drosophila ERK Rolled (Arg-80). Replacing this conserved Arg with Ser rendered these MAPKs intrinsically active to very high levels when tested in vitro as recombinant proteins. Combination of the Arg to Ser mutation with the sevenmaker mutation (producing Erk2(R65S+D319N) and Rolled(R80S+D334N)) resulted in even higher activity (45 and 70%, respectively, in reference to fully active dually phosphorylated Erk2 or Rolled). Erk2(R65S) and Erk2(R65S+D319N) were found to be spontaneously active also when expressed in human HEK293 cells. We further revealed the mechanism of action of the mutants and show that it involves acquisition of autophosphorylation activity. Thus, a first generation of Erk molecules that are spontaneously active in vitro and in vivo has been obtained.